REPRESENTATION OF WOMAN’S BODY IN PRESS AS SOCIALIZATION RISK FACTOR - Buzaitytė-Kašalynienė, Jolita; Rinkevičienė, Virgina (Acta Paedagogica Vilnensia, 2009)
Mass media represents social expectations for personal behavior and creates models and images to follow. The ideal image of the woman’s body and the impact of this image on adolescent girls’ perception of their own bodies has been analized in this paper. According to the theory of self-evaluation the perception of one’s own body depends on three interacting images: publicly demonstrated body ideal, objective evaluation of one’s own body and internalized body ideal. The publicly demonstrated body ideal has been revealed by analyzing women’s body images presented in pictures of most popular among adlencent girls’ magazines. Adolescent girls’ survey has helped to reveal objective mesures of girls’ bodies (body weight idex), and girls’ subjective perceptions of their own bodies Most of the analyzed pictures contained images fitting with anorexia nervosa body types. The survey revealed inconsistencies between objective body mesures and subjective body perceptions. Adolescents tended to percieve their bodies having bigger sizes then they realy were. Small body weight index girls tended to stay slim, or become even slimmer, and normal body weight index girls tended to become slimmer. It can be asumed that disatisfaction with bodies is provoked by internalized ideal of a very slim woman’s body. One third of girls admitted that their opinions towards their own bodies were negatively changing while observing slim models in magazines. The ideal of women’s body presented in magazines can be assumed as a risk factor for eating disorders in the process of socialization.